Valorization of local ethnobotanical knowledge in Ouled Ben Abdelkader region, Northwest of Algeria - Hedidi, Djahida; Zemmar, Nabila; Belabass, Meryem; Hamdani, Fatma Zohra; Belhacini, Fatima; Abaidia, Sofiane (Ethnobotany Research and Applications, 2024)
Background: This study aims to explore the ethnobotanical practices and to emphasize the local ethnobotanical knowledge of the indigenous population in the region of Ouled Ben Abdelkader, located in the Northwest of Algeria. Methods: The present ethnobotanical investigation was conducted during the period from November 2021 to April 2022, based on a sample of 269 participants. The collection of information on plants usage was based on semi-structured interviews. The collected data were subsequently analyzed through the calculation of several parameters, including the use value, the relative frequency of citation and the informant consensus factor for each plant. Results: Through this ethnobotanical survey, 100 species belonging to 44 botanical families were widely reported by the local population. Lamiaceae, Asteraceae and Apiaceae were the most dominant families with 14%, 10% and 8% respectively. Leaves and aerial parts were the most commonly used parts, with infusion and decoction being the most common techniques. Eucalyptus globulus and Origanum vulgare were the most frequently cited plants, while Pistacia lentiscus had the highest use value. The analysis of the data showed 13 distinct ailment categories, the respiratory system disorders and gastrointestinal system diseases exhibited the highest values with 0.94 and 0.92 respectively, suggesting that the respondents were in agreement regarding the potential therapeutic applications of medicinal plants against these specific ailments. Conclusions: As part of this study, the main objective was to enhance the ethnobotanical heritage of the population in this study area by envisaging promising opportunities in the field of pharmacology. Keywords: Ethnobotany, traditional medicine, valorization, quantitative indices, local population, Algeria.